An in silico analysis revealed a novel evolutionary lineage of putative mitoviruses - Jacquat, Andrés Gustavo (2022)
Mitoviruses (family Mitoviridae) are small capsid-less RNA viruses that replicate in the mitochondria of fungi and plants. However, to date, the only authentic animal mitovirus infecting an insect was identified as Lutzomyia longipalpis mitovirus 1 (LulMV1). Public databases of transcriptomic studies from several animals may be a good source for identifying the often missed mitoviruses. Consequently, a search of mitovirus-like transcripts at the NCBI Transcriptome Shotgun Assembly (TSA) library, and a search for the mitoviruses previously recorded at the NCBI non-redundant (nr) protein sequences library, were performed in order to identify new mitovirus-like sequences associated with animals. In total, 10 new putative mitoviruses were identified in the TSA database, and 8 putative mitoviruses in the nr protein database. To our knowledge, these results represent the first evidence of putative mitoviruses associated with poriferan, cnidarians, echinoderms, crustaceans, myriapods and arachnids. According to different phylogenetic inferences using the maximum likelihood method, these 18 putative mitoviruses form a robust monophyletic lineage with LulMV1, the only known animal-infecting mitovirus. These findings based on in silico procedures provide strong evidence for the existence of a clade of putative mitoviruses associated with animals, which has been provisionally named “kvinmitovirus”.